2010
DOI: 10.1002/hlca.200900378
|View full text |Cite
|
Sign up to set email alerts
|

Phosphomolybdic Acid (PMA)–SiO2 as a Heterogeneous Solid Acid Catalyst for the One‐Pot Synthesis of 2H‐Indazolo[1,2‐b]phthalazine‐triones

Abstract: Phosphomolybdic acid (PMA) -SiO 2 was found to be an efficient catalyst for the three-component condensation reaction of phthalhydrazide, 1,3-diketone, and aldehydes to produce 2H-indazolo[1,2-b]phthalazine-triones in excellent yields. The catalyst can be recovered and reused without significant loss of activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…In order to establish the real effectiveness of the catalyst for the synthesis of 2H-indazolo[2,1-b]phthalazine-trione derivatives, a comparative reaction was performed without catalyst using phthalhydrazide, benzaldehyde and dimidone in ethanol at reflux. It was found that only 35 % of product was obtained in the absence of catalyst even after 1 h ( [15][16][17][18][19][20][21]. When the reaction was performed under solvent free conditions, high yield of target product was obtained ( Table 1, entry 8).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In order to establish the real effectiveness of the catalyst for the synthesis of 2H-indazolo[2,1-b]phthalazine-trione derivatives, a comparative reaction was performed without catalyst using phthalhydrazide, benzaldehyde and dimidone in ethanol at reflux. It was found that only 35 % of product was obtained in the absence of catalyst even after 1 h ( [15][16][17][18][19][20][21]. When the reaction was performed under solvent free conditions, high yield of target product was obtained ( Table 1, entry 8).…”
Section: Resultsmentioning
confidence: 97%
“…Besides these they are endowed with anticonvulsant [6], cardio tonic [7] and vasorelaxant activities [8] and also comply as anti-inflammatory, analgesic, antihypoxic and antipyretic agents [9]. Numerous protocols have been developed for the synthesis of 3,4-dihydro-1H-indazolo [1,2-b]phthalazine-1,6,11(2H,13H)-triones using p-TSA [10], ionic liquids [11], (S)-CSA [12], dodecylphosphonic acid (DPA) [13], heteropoly acids [14], Ce(SO 4 ) 2 Á4H 2 O [15], solid acids [16], montmorillonite K-10 [17], N-halosulfonamides [11], silicasulfuric acid [18], phosphomolybdic acid-silica (PMA-SiO 2 ) [19] as catalysts. However, some of the synthetic strategies suffer from certain limitations such as expensive catalysts, low yields of products, long reaction times, use of toxic solvents, tedious procedures for preparation of catalysts and tedious work-up conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The recovered PEG 400 phase was reused for consecutive reactions. All products were characterized on the basis of their spectral analysis (IR, 1 H NMR, 13 C NMR and elemental analysis) and melting point determination [37,[57][58][59][60]. Hexyl (2q) Me 4s 4 63 a) Reaction conditions: phthalhydrazide 1 (1 mmol), aldehyde 2a-2q (1 mmol), cyclic β-diketone 3a, 3b (1 mmol); catalyst: CAN (5 mol%); T: 50°C; solvent: PEG 400 (2 mL).…”
Section: 2mentioning
confidence: 99%
“…In addition, these compounds show good promise as new luminescence materials and fluorescence probes [12]. There are several methods to synthesize phthalazine derivatives, including the reaction of phthalhydrazide, aldehydes and dimedone or cyclohexane-1,3-dione catalyzed by p-TSA [13], H 2 SO 4 [14], H 4 SiW 12 O 40 [15], H 3 PW 12 O 40 [16], silica sulfuric acid [17], silicasupported polyphosphoric acid [18], TMSCl [19], phosphomolybdic acid (PMA)-SiO 2 [20], N,N,N ,Ntetrabromobenzene-1,3-disulfonamide and poly(Nbromo-N-ethylbenzene-1,3-disulfonamide) [21]. Most recently a one-pot four-component reaction for the synthesis of phthalazine derivatives was reported using Ce(SO 4 ) 2 · 4H 2 O [22] as catalyst.…”
Section: Introductionmentioning
confidence: 99%